Slipped capital femoral epiphysis: an epidemiological Nationwide study in Italy from 2001 to 2015 - Umile Giuseppe Longo; Rocco Papalia; Sergio De Salvatore; Laura Ruzzini; Vincenzo Candela; Ilaria Piergentili; Leonardo Oggiano; Pier Francesco Costici; Vincenzo Denaro (BMC Musculoskeletal Disorders, 2021)
Abstract Background Slipped capital femoral epiphysis (epiphysiolysis of the femoral head, SCFE) is the most common pediatric hip disease in 10–14 years old children. The most used procedure to correct a stable form of SCFE is in situ pinning. Instead, the proper treatment for unstable forms is controversial. The first purpose of this study was to estimate annual admissions for SCFE in Italian patients from 2001 to 2015, basing on the hospitalization reports. The second aim was to assess the difference between regions regarding SCFE procedures. Lastly, a statistical prediction of the volume of SCFE procedures performed in Italy based on data from 2001 to 2015 was performed. Methods Data of this study were collected from the National Hospital Discharge Reports (SDO) reported at the Italian Ministry of Health regarding the years of this paper. The yearly number of hospital admission for SCFE, the percentage of males and females, the average age, days of hospitalization, primary diagnoses and primary procedures in the whole Italian population were calculated using descriptive statistical analyses. Results From 2001 to 2015, 4893 hospitalizations for SCFE were recorded in Italy, with a mean incidence of 2.9 (cases/100.000 inhabitants). The majority of patients treated by SCFE were males (70.6%). Conclusion National health statistics for SCFE are attractive for an international audience, as different approaches to screening are reported between countries. These differences allow comparing outcomes internationally. Moreover, sharing national statistics and correlating those to other countries protocols, could be helpful to compare outcomes for different procedures internationally. However, further studies are required to understand the specific reasons for regional variation for SCFE procedures in Italy. Level of evidence III